Cross-faculty analysis of AI-enhanced civic character education on digital citizenship development - Warlim, Warlim; Effendi, Ridwan; Fitria, Ratna; Ibrahim, Mujizat Maulana; Hadiati, Diah Nur (Frontiers in Education, 2026)
IntroductionDigital transformation has transformed the educational landscape, demanding a reconceptualization of character education within a technological framework aligned with global competency standards. This study examines the effectiveness of AI-enhanced civic character education in developing character competencies and digital citizenship across various disciplinary contexts.MethodsThis mixed-methods experimental study employed a 2 × 2 factorial design involving 240 students from the Faculty of Engineering Education (n = 120) and the Faculty of Language and Literature Education (n = 120). Implementation was conducted over 18 sessions (February–June 2024) using an AI platform integrated with Pancasila values. Data were collected through the Civic Character Scale, the Digital Citizenship Competency Scale, and semi-structured interviews, analyzed using repeated measures ANOVA and structural equation modeling.ResultsAI-enhanced civic character education demonstrated significant effectiveness in improving civic character competencies (d = 0.51) and digital citizenship (d = 0.73) compared to traditional learning. Mediation analysis revealed that digital citizenship served as a fundamental mediating pathway (47.4% of the total effect) between AI engagement and character development. The differences in responses across faculties were significant: engineering students were more responsive to the structured AI feedback system, while humanities students benefited more from the reflective digital citizenship experience.Discussion/ConclusionThis study establishes AI-based civic character education as an effective approach, with differing patterns of mediation across faculties. These findings challenge universal approaches to AI implementation, favoring differentiated strategies that respect epistemological diversity while achieving coherent educational outcomes. The successful integration of Pancasila values demonstrates an educational technology pathway that supports local cultural wisdom. The semester-based implementation provides a replicable template for global adoption with appropriate cultural adaptations.